Aptamer-assisted tumor localization of bacteria for enhanced biotherapy - Zhongmin Geng (Nature Portfolio, 2021)
Bacteria-based therapy has shown promise for cancer treatment. To enhance tumor accumulation, here the authors describe the design of tumor specific aptamer-conjugated bacteria, to improve intratumor localization and enhance therapeutic efficacy.